Enhancing Critical Thinking Skills Through Problem-Based Learning: A Classroom Intervention in Junior High School - Solehuddin, Moh; Sartinayanti, Sartinayanti; Hasnah, Sitti; Karmila, Mila; Muriyanto, Muriyanto (International Journal of Educational Research Excellence, 2025)
This study explores the implementation of Problem-Based Learning (PBL) as an effective classroom intervention to enhance critical thinking skills among junior high school students in Indonesia. Using a qualitative approach with a pretest-posttest design, the intervention engaged ninth-grade students in collaborative problem-solving activities integrated into their regular curriculum. Data collected from standardized critical thinking assessments, observations, and student work showed significant improvement in students’ critical thinking abilities after the PBL intervention. Specifically, students demonstrated enhanced analytical reasoning, argument analysis, and evidence-based evaluation skills, with average posttest scores rising from less critical to critical categories, reflecting improvements of over 20% across key indicators. Observations also revealed increased student engagement, collaboration, and confidence in articulating solutions. Despite challenges such as teacher preparedness, time constraints, and uneven participation, the study highlights the transformative potential of PBL in fostering higher-order thinking skills. Recommendations include targeted professional development, structured scaffolding, and leveraging technology to optimize implementation. These findings support PBL as a valuable pedagogical strategy to cultivate critical thinking, preparing junior high school students for complex problem-solving demands in the 21st century.